The programme of the Swedish Social Democratic Labour Party : adopted by the Congress of the Party held in Stockholm, June 1960. - Sveriges Socialdemokratiska Arbetareparti (SAP) (Hälsingborg : Nyheterna, 1960)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: arbeiderspartij; Zweden